DEGENERATIVE SCOLIOSIS: A CASE REPORT - I Ketut Martiana; M Mukaddam Alaydrus (Journal Orthopaedi and Traumatology Surabaya)
Background: Scoliosis in adults is a spinal deformity in adult patients with a Cobb angle of more than 10° in the coronal plane. Degenerative scoliosis is a term used for the presence of spinal coronal deviation in the elderly population due to segment degeneration. This case report presents a quite different management option, namely applying intraoperative vertebral correction to the subject. The operative procedure carried out on the patient has experienced success as indicated by improvement in symptoms and curve progressiveness in patients.